Gurli Jakobsen and Jens Erik Torp (ed.). Understanding Business Systems in Developing Countries. New Delhi: Sage Publications, 2001. Paperback. 260 pages. Indian Rs 225.00. (The Pakistan Development Review, 2001)
Edited by Gurli Jakobsen and Jens Erik Torp, Understanding Business Systems in Developing Countries strives to do just that by presenting the views of scholars in the field of development economics. Analyses of developing business systems at the international, national, and sector levels provide the reader with significant insight into how economies actually function. The dominant paradigm within which these analyses take place is that of growth-oriented capitalistic development. Richard Whitley’s study of emerging capitalistic economies and Henrik Schaumburg-Mueller’s study of firms in the developing world represent the international level studies. Their overviews provide some interesting perspectives on the response of the private sector to structures at the national and international levels.